Intervention strategies for improvement of disasters risk perception: Family-centered approach - Hesam Seyedin; Ezat Samadipour; Ibrahim Salmani (Wolters Kluwer Medknow Publications, 2019)
Introduction: Today, the role of people in crisis management plans is of particular importance due to the prepared community approach. It is difficult or impossible to attract public involvement due to the low level of public perception of risk. Therefore, it is necessary to discover the status of risk perception and its affecting factors. This study was conducted to investigate factors affecting the strategies of disaster risk perception improvement. Materials and Methods: This systematic review study was conducted in 2017 using extensive electronic and library literature searches in the Web of Science, Scopus, and PubMed electronic databases. The preliminary findings included 1030 studies. Out of 941 retrieved references, 925 references were excluded because they did not meet the objectives of this review or did not focus directly on general population. Finally, 16 articles were selected for further investigation. Results: The extracted variables were divided into four general domains: personal, psychological, socioeconomic, and cultural factors. Personal characteristics included sex, age, marriage, level of education, personal knowledge, and disaster personal experience. Psychological factors comprised emotions (fear and insecurity), mental images (beliefs, attitudes), and internal and external control. Cultural factors such as, belief, values, norms, faith, religious, and protective spirit were effective in general perception of disasters risk. Socioeconomic factors such as, income, livelihood, insurance coverage, trust, and fair access to land and resources were also influential. The strategies to improve public disaster risk perception were educational, participatory, incentive, confidence building, supportive, managerial and cultural ones. A family-centered approach is recommended for the better implementation of strategies. Conclusion: The improvement of risk perception requires government planning in different fields such as education, research, health, and culture, with an emphasis on social groups especially family.